Red Cell Distribution Width Is Positively Correlated with Atherosclerotic Cardiovascular Disease 10-Year Risk Score, Age, and CRP in Spondyloarthritis with Axial or Peripheral Disease. (27th September 2018) - Ahmad, Hassan; Khan, Mariam; Laugle, Michelle; Jackson, Desmond A.; Burant, Christopher; Malemud, Charles J.; Askari, Ali D.; Mattar, Maya; Blumenthal, David E.; Zidar, David A.; Anthony, Donald D.
Abstract : Background . Red blood cell distribution width (RDW) is a routine hematologic parameter that is a predictor of cardiovascular disease (CVD) events and is independent of combined traditional risk factor scoring systems. The RDW has also been associated with rheumatic disease activity. Whether RDW is associated with traditional CVD risk factors or Atherosclerotic Cardiovascular Disease (ASCVD) 10-year CVD risk score in patients with seronegative spondyloarthritis with axial or peripheral disease has not been previously determined. Methods . We performed a retrospective, chart review study evaluating the relationship between RDW, albumin, hemoglobin, C-reactive protein (CRP), absolute lymphocyte count (ALC), and ASCVD scoring parameters [age, hypertension status, diabetes mellitus (DM) status, lipid profile, and smoking status] in a cohort of spondyloarthritis patients, taking into consideration their HLA-B27 status, race, and treatment status. Results . RDW was found to positively correlate with ASCVD 10-year score and age, and ASCVD score did not change over time after patients were treated for spondyloarthritis. Albumin was found to negatively correlate with ASCVD 10-year risk score. Both RDW and albumin correlated with CRP. ALC failed to correlate with ASCVD 10-year score but did show a tendency to be associated with CVD, CVD events, and cardiac conduction abnormalities. Conclusions . These data indicate that further study is warranted to evaluate RDW, albumin level, and ALC as potential predictors of CVD in the spondyloarthritis patient population.